Flare‐up of generalized pustular psoriasis combined with systemic capillary leak syndrome after coronavirus disease 2019 mRNA vaccination. Issue 4 (3rd December 2021) - Yatsuzuka, Kazuki; Murakami, Masamoto; Kuroo, Yuta; Fukui, Maiko; Yoshida, Satoshi; Muto, Jun; Shiraishi, Ken; Sayama, Koji
Abstract: Generalized pustular psoriasis (GPP) is characterized by acute flare‐ups induced by various factors, but few reports have described GPP onset or flare‐up induced by vaccination. To our knowledge, only three such cases following coronavirus disease 2019 (COVID‐19) vaccination have been reported. We herein report a case of GPP flare‐up after COVID‐19 mRNA vaccination. A 65‐year‐old man with GPP controlled by infliximab presented with widespread pustular erythema, fever, and malaise following his second COVID‐19 mRNA vaccination. A skin eruption was apparent at the injection site. He also exhibited systemic capillary leak syndrome (SCLS), which responded rapidly to secukinumab and systemic corticosteroids. Two biopsies, one of which was of the injection site, revealed not only findings typical of GPP, but also a dermal mixed‐cell infiltration with eosinophils, and microthrombi in the small dermal vessels. The latter findings have been observed in cutaneous lesions induced by both COVID‐19 infection and vaccination. This is the first case of a GPP flare‐up accompanied by SCLS induced by a COVID‐19 mRNA vaccine. Also, this is the first flare‐up induced by the second vaccine dose, and the first such report including detailed histological data, including for the injection site.